Study of spatial-temporal peculiarities of the animal husbandry development in Ukraine - Melnychenko , S. G.; Bohadorova , L. M. (Man and Environment. Issues of Neoecology, 2022)
For several decades, negative trends have been visible in animal husbandry, which in the future may become prerequisites for a food crisis on the territory of Ukraine. That is why the study of spatial-temporal dynamics, as well as the selection of areas of specialization of individual branches of the animal husbandry sector, is quite important and relevant.Purpose. To study the specialization of the animal husbandry complex of Ukraine and to identify sectoral disproportions in animal husbandry in the regions of Ukraine.Methods: Statistical,  cartographic, comparative-geographical.Results. We have collected and analyzed the statistical materials of the Main Department of Statistics regarding livestock in the animal husbandry industry in Ukraine for 2009 and 2019. It was found that in all branches, except for poultry, there is a noticeable tendency to reduce livestock. On the basis of the collected statistical data, coefficients of specialization in the animal husbandry industry were calculated. According to the results of the calculations, maps were developed, on which the spatial-temporal trends of changes in the areas of specialization of the branches of the animal husbandry complex of Ukraine were highlighted.  We identified the main reasons that negatively affected the development of animal husbandry in Ukraine, which included: insufficient state and financial support for the industry; decrease in the share of the rural working population; lack of subsidies for the animal husbandry industry; unprofitability of production; outdated material base and labor-intensive production.Conclusions. According to the research results, it was found that the livestock number in the animal husbandry industry has a tendency to decrease over the last ten years. Positive dynamics are present only in the poultry industry.Identifying the reasons that led to negative trends in animal husbandry became a further basis for developing solutions that could solve these problems. These include: financial support of the industry and attraction of investments; state subsidies; development of selection and breeding business; updating the material and technical base.